Who put the Holes in the Swiss Cheese? Currency Crisis Under Appreciation Pressure - Kristin Berthold; Georg Stadtmann (Journal of Central Banking Theory and Practice, 2018)
We examine the reasons why the SNB gave up the lower floor of the 1.20 CHF/EUR exchange rate arrangement. Three types of shocks played a role: Exogenous shocks to the autonomous component of money demand, interest rate decreases of the ECB, as well as appreciation expectations. In order to defend these shocks, the SNB intervened heavily in the foreign exchange market. This led to an accumulation of reserves in the central bank's balance sheet of the size of 80% of Swiss GDP. Interestingly, the SNB did not lower the interest rate into the negative range during the time period where the peg was in place. Hence, the SNB did not do "whatever it takes" to defend the peg.
Keywords: E52; E58; E42; 330; Foreign exchange market; Swiss crisis; UIP; Currency crisis.